Electrical and optical enhancement of ITO/Mo bilayer thin films via laser annealing - Hacini, Abdelbaki; Hadi Ali, Ahmad; Adnan, Nurul Nadia; Nayan, Nafarizal (Beilstein Journal of Nanotechnology, 2022)
ITO/Mo bilayer thin films were sputtered on n-type silicon and glass substrates and annealed with a Nd:YAG pulsed laser. The structural results show that both the as-deposited and the annealed ITO/Mo thin films have a polycrystalline structure, and that the annealing treatment enhanced the crystallinity of samples. Moreover, the XRD patterns exhibited a cubic structure preferentially oriented along the (222) and (400) planes. The AFM analysis shows that grain size and RMS roughness increased from 16.02 to 36.19 nm and 0.4 to 2.6 nm, respectively, when the laser energy was increased to 120 mJ. The as-deposited sample has an optical transmittance of nearly 80% in the 300–800 nm range. The laser annealing yielded a higher transmittance of 94% and increased the bandgap energy from 2.76 to 2.88 eV at 120 mJ. The annealing treatment decreased the resistivity from 15.63 × 10−4 to 1.73 × 10−4 Ω/cm−1. Additionally, the figure of merit of the ITO/Mo structure improved significantly from 6.63 × 10−4 Ω−1 of the as-deposited sample to 17.6 × 10−3 Ω−1 of the the annealed structure. The results indicate that the laser annealing could improve the efficiency of the transparent conductive layer, which can be potentially applied in optoelectronic devices.
Keywords: indium tin oxide (ITO); laser annealing; molybdenum (Mo); Nd:YAG